Legal Protection for Unregistered Clothing Design on Marketplace: Comparison Between the Indonesian and the UK Law - Nuzulia Kumala Sari; Emi Zulaika; Rania Devayanti (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2022)
The industrial design protection system in Indonesia uses registration requirements, without registration, there is no protection. This is in contrast to the UK’s existing industrial design protection system, where the UK implements two protection systems, namely the registered design right or unregistered design right. This unregistered protection system is used in products that do not last long on the market such as fashion products and as an alternative for companies to test design prospects on the market. Unregistered protection systems are also used as design protection alternatives to prevent copying or plagiarizing of designs that do not yet have registration numbers. This article will discuss the following issues: 1) The legal protection of Korean pop idol clothing designs is reviewed based on Indonesian and English laws; and 2) The urgency of legal novelty in the industrial design law in Indonesia. In this study, the legal research method used is normative legal research with an approach through statutory regulations, a conceptual approach, and a comparative approach. The legal materials used are primary legal materials and secondary legal materials. The conclusion is that the industrial design protection system in Indonesia still has to go through the registration process, this is irrelevant to products or goods that cannot last long in the market because trends change easily. This is different from that in the UK where it implements an unregistered design right system where industrial design rights are obtained automatically.